Niger : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility; Staff Report; Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Third Review Under the Extended Credit Facility (ECF) for Niger. Program implementation to date is satisfactory and all quantitative performance criteria at end-June 2009 were met. The revenue performance is strong and domestic arrears repayment higher than anticipated. All indicative targets at end-September were observed, confirming these trends. On the structural front, the authorities have implemented measures to strengthen debt management, improve budget monitoring, and enhance the business environment.